Faktor-Faktor yang Memengaruhi Profitabilitas Sub Sektor Food dan Beverage - Putri, Azzahra Whidniessa; Kharismar, Emir; Wahyudi, Agustinus Sri; Beny (Media Bisnis, 2025)
This observes pursuits to determine monetary factors such as current ratio, debt to equity ratio, company size, decision of investment, and total assets turnover that affect profitability in companies in Indonesia for the duration 2017-2023. This research was performed again because of the inconsistency of the outcomes of previous research. The object used on this have a look at is the food and Beverage subsector company indexed on the Indonesian stock exchange for the duration 2017-2023. The sample in this examination consisted of 26 corporations with 182 information decided on using purposive sampling technique. The statistics became processed and examined the use of Eviews 10 panel statistics regression with a random impact model for hypothesis testing. The consequences showed that current ratio, debt to equity ratio, and company size have no giant effect on profitability. In evaluation, decision of investment, and total assets turnover have a vast impact on profitability. This finding confirms the significance of asset management performance and strategic investment decisions in assisting company economic overall performance.